2018
DOI: 10.30560/mhs.v1n1p8
|View full text |Cite
|
Sign up to set email alerts
|

Health Outcomes in Sub-Saharan Africa Countries: An Analysis of Key Determinants

Abstract: The poor health outcomes (low longevity and high mortalities) in developing countries has been great concern for citizens and policy makers alike. Although, numerous studies have focus on socio-economic drivers (like education, age of mothers, income levels, and poverty) of health outcomes in developing nations; however, the same is not true for important exogenous determinants. Therefore, this study investigated the effects of access to clean drinkable water, sanitation, fertility rate, prevalence of HIV/AIDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Limited research has evaluated the PHS–PHO relationship in developing regions, notably SSA, where results have been inconclusive. Some SSA studies have shown that PHS improves PHO [ 23 , 51 , 52 , 61 ], but others have not [ 2 , 18 , 33 , 57 ]. Most of these studies have solely examined the ultimate impact of the PHS on PHO as evaluated by mortality-based indicators, such as under-5-years mortality and life expectancy.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Limited research has evaluated the PHS–PHO relationship in developing regions, notably SSA, where results have been inconclusive. Some SSA studies have shown that PHS improves PHO [ 23 , 51 , 52 , 61 ], but others have not [ 2 , 18 , 33 , 57 ]. Most of these studies have solely examined the ultimate impact of the PHS on PHO as evaluated by mortality-based indicators, such as under-5-years mortality and life expectancy.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Some of the studies proved no relationship between health care expenditures and its outcome. For instance, for the years 1995 -2013, the effect of public health expenditure on health outcomes was studied by Popoola [18] in Tanzania. A full Bayesian time series approach was used and results showed that government health expenditure had no impact on health outcomes like an infant and under-five mortality.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…The exact association between the PHS and population health outcomes in SSA is ambiguous. Some studies have indicated that PHS is effective in improving population health outcomes (Nyamuranga & Shin, 2019;Arthur & Oaikhenan, 2017;Oladosu et al, 2022), whereas others maintain that it is not (Akinlo & Sulola, 2019;Popoola, 2018).…”
Section: Empirical Reviewmentioning
confidence: 99%
“…For example, Popoola (2018) and Ogungbenle et al (2013) discovered that PHS did not affect neonatal mortality, under-five mortality, or life expectancy at birth (Ogungbenle et al, 2013;Popoola, 2018). Furthermore, using the GMM method, Kamiya (2010) analysed the factors contributing to child mortality in low-income countries, including SSA, and discovered that higher PHS levels did not reduce child mortality (Kamiya, 2010).…”
Section: Empirical Reviewmentioning
confidence: 99%